Giant Retinal Tears in Children: Associations and Outcomes - Syed Ali Haider, Qasim Lateef Chaudhry (Pakistan Journal of Ophthalmology, 2009)
Purpose: Giant Retinal Tear (GRT) as a cause of retinal detachment is uncommon in children. Their associations and surgical outcome in children of 16 years and less are not well described. Material and Methods: All patients who presented with retinal detachment due to GRT between 1998 and 2004 were included in the study. They underwent 3 ports Pars Plana Vitrectomy, 360 encirclement with 2.5 mm band and fluid perfluorocarbon liquid silicone oil exchange. Results: 12 patients, 8 boys and 4 girls with an age range of 5-16 years presented and underwent surgery during this period. High myopia, Sticklers’ syndrome, Weil Marchisani syndrome, trauma and Anterior Segment Cleavage disorder were the principal associations. In five patients the fellow eye was already NPL due to chronic retinal detachment. 7 patients had minimal or no PVR (Proliferative Vitreo-retinopathy) while the others ranged from stage B to C2 PVR. While all except one retina were re-attached per-operatively, at six months only 4 retinas remained fully attached. Both children under 10 years of age had a poor outcome. Conclusion: Retinal detachment, due to GRT, in children often has poor outcome due to aggressive evolution of PVR and difficulty in posturing. Younger age may be associated with poorer outcome